PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN PERHOTELAN DAN PARIWISATA DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Robiyanto, Robiyanto; Nafiah, Ilma; Harijono, Harijono; Inggarwati, Komala (LP2M Institut Teknologi dan Bisnis Asia Malang, 2020)
This study aims to examine the effect of profitability on firm value with capital structure as an intervening variable. The population of this study is hotel, restaurant and tourism firms listed on the Indonesia Stock Exchange (IDX), during 2012-2016, with 75 samples selected by using purposive sampling. Analysis of this study using panel regression analysis. This study of the research show that (1) profitability as measured by ROA and ROE has a negative and significant effect on firm value as measured by PBV and profitability as measured by ROA and ROE has a negative and insignificant effect on firm value as measured by Tobin's Q, (2) profitability has a negative and significant effect on the capital structure, (3) the capital structure as measured by DER has a positive and significant effect on firm value as measured by PVB and the capital structure as measured by DER has a positive and insignificant effect on company value as measured by Tobin's Q and (4) capital structure as an intervening variable negatively influences the effect of profitability on firm value.